(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Many physiological factors such as ethnicity, sex and blood group have been proven to have roles to play in determining the bleeding and clotting time of an individual. Earlier studies had conflicting results about the bleeding and clotting time in an individual concerning physiological factors. The objective of the study was to study the bleeding and clotting time of an individual with respect to their sex and blood group. This cross-sectional study involved 134 undergraduate students between the ages of 17-25years. Blood group was determined using a standard anti-sera, clotting time was determined using the capillary method while the bleeding time was determined using Duke’s filter paper method. In this study, blood group B was predominate. The bleeding time and clotting time were significantly longer in females compared to that of males. The clotting time was longer in individuals with blood group O but the bleeding time among the blood groups was not significantly different. However, the subject size needs to be increased in further studies.